The Relationship Between Sodium Intake, Stress Levels, and Blood Pressure Among Production Employees at PT Eurochair Internusa - Davena Zulkurnia; Desty Muzarofatus Sholikhah (Mitra Akademia Indonesia, 2026)
Hypertension is one of the most prevalent non-communicable diseases and remains a major public health concern among productive-age populations. Sodium intake and psychological stress are considered important modifiable factors associated with changes in blood pressure. This study aimed to analyse the relationship between sodium intake and stress levels and blood pressure among production employees at PT Eurochair Internusa. An analytical observational study with a cross-sectional design was conducted involving 74 production employees selected through purposive sampling. Sodium intake was assessed using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), stress level was measured using the Depression Anxiety Stress Scale (DASS-21), and blood pressure was measured using an Omron JPN600 digital sphygmomanometer. Data were analysed using the Spearman Rank correlation test with a significance level of p<0.05. The results showed a significant positive relationship between sodium intake and systolic blood pressure (p=0.003; r=0.344), while no significant relationship was found between sodium intake and diastolic blood pressure (p=0.379). Stress level was not significantly associated with systolic blood pressure (p=0.336), but showed a significant positive relationship with diastolic blood pressure (p<0.001; r=0.407). The novelty of this study lies in examining the combined influence of sodium intake and stress level on blood pressure among manufacturing production employees, a population that has received limited attention in previous studies. These findings suggest that controlling sodium intake and implementing workplace stress management programs may help maintain normal blood pressure and prevent hypertension among employees.